Crystalline microstructure and dielectric properties of oriented poly(ethylene-co-tetrafluoroethylene). (24th March 2017) - Huang, Yun; Miranda, Daniel F.; Iacob, Ciprian; Zhang, Shihai; Runt, James
Abstract: In the present investigation, we explore the influence of uniaxial orientation and subsequent thermal annealing on semi-crystalline poly(ethylene-tetrafluoroethylene) (ETFE) microstructure and dynamics, and the connection to dielectric breakdown strength. Understanding the influence of crystalline microstructure on dynamics and breakdown, and in turn how processing influences microstructure, is critical for establishing rational design of polymer dielectrics. When drawn below the glass transition temperature (Tg ), the Weibull breakdown strength decreases compared to that of the undrawn precursor film, but increases on thermal annealing near or above Tg . This behavior is associated with the formation and elimination of drawing-induced microvoids, respectively. When drawn above Tg, the breakdown strength increases to ∼870 MV/cm, dominated by orientation of amorphous segments, and decreases on thermal annealing above Tg to near that of the undrawn film. Graphical abstract: Highlights: Uniaxial drawing alters crystalline microstructure and segmental dynamics of ETFE. Annealing near or above Tg relaxes oriented amorphous segments, but has no significant effect on lamellar orientation. Dielectric breakdown strength increases with uniaxial orientation to values as high as 870 MV/cm.